Hepatitis B Virus Testing and Care among Pregnant Women Using Commercial Claims Data, United States, 2011-2014 - Aaron M. Harris; Cheryl Isenhour; Sarah Schillie; Claudia Vellozzi (Hindawi Limited, 2018)
Introduction. Pregnant women should receive hepatitis B virus (HBV) testing with hepatitis B surface antigen (HBsAg), but it is unclear whether HBV-infected pregnant women are linked to care. Methods. We analyzed MarketScan™ commercial insurance claims. We included pregnant women, aged 10-50 years, with 42 weeks of continuous enrollment before (predelivery) and 6 months after (postdelivery) the first delivery claim for each unique pregnancy between 1/1/2011 and 6/30/2014. We identified claims for HBsAg testing by CPT code and described the care continuum among pregnancies with an associated ICD-9 HBV diagnosis code by demographic and clinical characteristics, including HBV-directed care ([HBV DNA or hepatitis B e antigen] and ALT test codes) and antiviral treatment (claims for tenofovir, entecavir, lamivudine, adefovir, or telbivudine) pre- and postdelivery. Results. There were 870,888 unique pregnancies (819,752 women) included. Before delivery, 714,830 (82%) pregnancies had HBsAg test claims, but this proportion decreased with subsequent pregnancies (p<0.0001): second (80%), third (71%), and fourth (61%). We identified 1,190 (0.14%) pregnancies with an associated HBV diagnosis code: most were among women aged ≥ 30 years (76%) residing in the Pacific (34%) or Middle Atlantic (18%) regions. Forty-two percent of pregnancies with an HBV diagnosis received HBV-directed care (42% predelivery and 39% postdelivery). Antiviral treatment was initiated before delivery in 128 (13%) of 975 pregnancies and postdelivery in 16 (1.6%) pregnancies. Conclusions. While most of these commercially insured pregnant women received predelivery HBV screening, we identified gaps in HBV testing and the HBV care continuum which highlight potential targets for public health interventions.